Isolation of Aeromonas hydrophila from EUS Affected Shing Heteropneustes fossilis of a Fish Farm in Mymensingh - Rashid, MM; Hasan, MA; Mostafa, K; Islam, MA (Progressive Agriculture, 2013)
Aeromonas hydrophila bacteria was isolated from the suspected EUS-affected shing fish, Heteropneustes fossilis (Bloch). The disease investigations were primarily based on clinical signs and subsequently confirmed by the isolation of bacterial pathogen Aeromonas hydrophila from lesion of liver and kidney. The A. hydrophila isolates were identified by a series of morphological, physiological and biochemical tests. The total bacterial load in liver, intestine and kidney were 1.67 × 104 to 6.46 × 108 CFU/g, 1.71 × 103 to 1.18 × 109 CFU/g and 1.47 × 104 to 3.70 × 108 CFU/g respectively. DOI: http://dx.doi.org/10.3329/pa.v19i1.17362 Progress. Agric. 19(1): 117 - 124, 2008